Transient pulsed discharge preparation of graphene aerogel supports asymmetric Cu cluster catalysts promote CO2 electroreduction - Kaiyuan Liu; Hao Shen; Zhiyi Sun; Qiang Zhou; Guoqiang Liu; Zhongti Sun; Wenxing Chen; Xin Gao; Pengwan Chen (Nature Communications)
Abstract Designing asymmetrical structures is an effective strategy to optimize metallic catalysts for electrochemical carbon dioxide reduction reactions. Herein, we demonstrate a transient pulsed discharge method for instantaneously constructing graphene-aerogel supports asymmetric copper nanocluster catalysts. This process induces the convergence of copper atoms decomposed by copper chloride onto graphene originating from the intense current pulse and high temperature. The catalysts exhibit asymmetrical atomic and electronic structures due to lattice distortion and oxygen doping of copper clusters. In carbon dioxide reduction reaction, the selectivity and activity for ethanol production are enhanced by the asymmetric structure and abundance of active sites on catalysts, achieving a Faradaic efficiency of 75.3% for ethanol and 90.5% for multicarbon products at −1.1 V vs. reversible hydrogen electrode. Moreover, the strong interactions between copper nanoclusters and graphene-aerogel support confer notable long-term stability. We elucidate the key reaction intermediates and mechanisms on Cu4O-Cu/C2O1 moieties through in situ testing and density functional theory calculations. This study provides an innovative approach to balancing activity and stability in asymmetric-structure catalysts for energy conversion.